Andrographolide restores glucose uptake in rat hippocampal neurons - Gherardelli, Camila; Cisternas, Pedro; Gutierrez, Joel; Martinez, Milka; Inestrosa, Nibaldo C. (My University, 2021)
Cerebral glucose hypometabolism is a common pathophysiological characteristic of many neurodegenerative diseases. This metabolic dysfunction includes alterations in glucose transport from the blood into the neurons by the facilitative glucose transporters (GLUTs). Several studies suggest that metabolic disturbances precede clinical symptoms and correlate with disease progression. Some groups have started to explore the use of therapeutic strategies that target decreased cerebral glucose metabolism to promote its availability. We selected Andrographolide (Andro), a natural product obtained from Andrographis paniculate that has both anti-hyperglycemic and anti-diabetic effects. Although it was shown to promote glucose uptake in vivo, the underlying mechanisms remain unclear. Here, we evaluated the acute effects of Andro on glucose transport and metabolism using primary rat hippocampal neuronal cultures. Our results showed that Andro enhances neuronal glucose uptake and stimulates glucose metabolism by inducing GLUT3 and 4 expression in neurons, as well as by promoting glycolysis. We also observed that Andro-mediated effects depend on the activity of AMP-activated protein kinase (AMPK), one of the central regulators of glucose metabolism. Our studies open the possibility to use Andro as a drug to restore glucose levels in neurodegenerative diseases.
Keywords: ampk; andrographolide; glucose metabolism; glucose transport and glut expression